Rivaroxaban alleviates hepatic sinusoidal obstruction syndrome in mice by modulating the gut microbiota and inhibiting the PI3K/Akt signaling pathway - Liu, Wencheng; Cheng, Yanbin; Han, Xue; Xia, Junlin; Wei, Qingyu; Chang, Bing; Li, Quansheng (Frontiers in Microbiology, 2025)
IntroductionHepatic sinusoidal obstruction syndrome (HSOS) is a vascular liver disease with a high mortality rate, and treatment methods are limited. Rivaroxaban is an oral anticoagulant. This study aimed to investigate the pharmacological effect and potential mechanism of rivaroxaban on HSOS.MethodsIn this study, we induced an HSOS mouse model in male C57BL/6J mice by administering monocrotaline orally. The mice were randomly divided into four groups: the control group, the rivaroxaban (RIV) group, the monocrotaline (MCT) group, and the monocrotaline + rivaroxaban (MCT + RIV) group. Liver function and histopathology were evaluated. 16S rDNA sequencing of the small intestinal contents, transcriptomic sequencing of small intestine tissues, real-time qPCR, Western blot analysis of liver tissues, and correlation analysis were conducted. Antibiotic (ABX) treatment and fecal microbiota transplantation (FMT) experiments were also performed to explore the role of the gut microbiota.ResultsCompared with the MCT group, rivaroxaban alleviated serum biochemical liver function analysis and liver histopathology in the MCT + RIV group. Additionally, 16S rDNA sequencing of the small intestinal contents revealed that, compared with the MCT group, the MCT + RIV group presented increased relative abundances of Allobaculum and Pediococcus but decreased relative abundances of Streptococcus, Staphylococcus, and Candidatus Arthromitus. Mechanistically, integrated analyses, including transcriptomic sequencing of small intestin e tissues, real-time qPCR, Western blot analysis of liver tissues, and correlation analysis, demonstrated that rivaroxaban protected against MCT-HSOS by inhibiting the PI3K/Akt signaling pathway. In addition, antimicrobial cocktail (ABX) treatment eliminated the beneficial effects of rivaroxaban on liver function and histopathological injury, whereas fecal microbiota transplantation (FMT) from rivaroxaban-treated donors significantly ameliorated liver dysfunction and histological damage in MCT-HSOS mice.DiscussionThese findings suggest that rivaroxaban alleviates hepatic sinusoidal obstruction syndrome in mice by modulating the gut microbiota and inhibiting the PI3K/Akt signaling pathway. Rivaroxaban may be a promising therapeutic option for treating HSOS.